Kepuasan Klien Dengan Komunikasi Terapeutik Perawat Rumah Sakit Kepolisian Pusat Raden Said Soekanto - Muhammad Fandizal; Duma Lumban Tobing; Evin Novianti (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: to identify Relationship between attitude and therapeutic communication techniques with the level of client satisfaction.Methods: This article use Cross-sectional study design from descriptive-analytic research type. The measuring instrument uses 25 questionnaires. The number of samples in this study was 209 clients from a total of 442 clients. Data analysis using Chi-Square and Gamma Test.Results: Â The level of client satisfaction with nurses' therapeutic communication techniques and attitudes was 53.10%. A positive attitude of nurses in therapeutic communication 64.6% of clients expressed satisfaction, while 65.2% of clients were satisfied with good techniques in nurse therapeutic communication. There is a Relationship between Attitudes and Therapeutic Communication Techniques with Client Satisfaction Levels with Ï 0,001 and 0,000.Conclusion: Â There is a significant and strong enough relationship between attitude and techniques therapeutic communication with the level of client satisfaction.